2012
DOI: 10.1002/ejlt.201100239
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of conjugated linoleic and linolenic acids in fermented foods: Technological bottlenecks

Abstract: Several food-grade bacteria are known to produce conjugated linoleic acid (CLA) and conjugated linolenic acid (CLNA) from linoleic acid (LA) and a-linolenic acid (ALA), respectively. Therefore, bifidobacteria and a Lactobacillus sakei strain, able to produce CLA and CLNA in vitro, were applied as starter cultures for the fermentation of milk and meat, respectively. However, for both the fermented milk and meat no increase in CLA and CLNA content was obtained. Although LA and ALA were present in sufficient amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…The introduction of CLA into the diet did not significantly ( P > 0.01) affect the salami chemical composition, pH and a w both in Fabriano e Ciauscolo (Table ). These results are in agreement with previous studies who found that the incorporation of CLA into heavy pig diet did not modify the chemical composition of dried cured ham .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The introduction of CLA into the diet did not significantly ( P > 0.01) affect the salami chemical composition, pH and a w both in Fabriano e Ciauscolo (Table ). These results are in agreement with previous studies who found that the incorporation of CLA into heavy pig diet did not modify the chemical composition of dried cured ham .…”
Section: Resultssupporting
confidence: 94%
“…The administration of CLA‐enriched diets to pigs did not seem to interfere with the microbial evolution of the products. Furthermore, many strains of Lactobacilli , Lactococci and Streptococci are able to produce CLA from linoleic acid , therefore, improving functionality through CLA microbial biosynthesis in dry‐fermented meat products needs further consideration .…”
Section: Resultsmentioning
confidence: 99%
“…lactis in combination with S. thermophilus, was slightly higher than the CLA concentration of the starting milk (88,93,94). In contrast, there was no formation of CLA in fermented milks with strains of Bifidobacterium, despite having been chosen for their ability to produce CLA in vitro, and being cultured in substrates rich in linoleic acid (89).…”
Section: Cla In Fermented Milksmentioning
confidence: 87%
“…As stated by Van Nieuwenhove et al (2007), different strains tolerate different concentrations of LA. Additionally, the inhibitory dose depends on the availability of the FA (Gorissen, Raes, De Smet, De Vuyst, & Leroy, 2012;Trigueros & Sendra, 2015). According to Kim and Liu (2002), the growth of Lactococcus lactis was completely inhibited at LA concentrations higher than 0.50 mg/mL.…”
Section: Influence Of La Concentration On Bacterial Growthmentioning
confidence: 99%
“…According to Gorissen et al (2011), the conversion of CLA depends on the amount of free LA in the medium. Gorissen et al (2012) used Bifidobacteria and Lactobacillus sakei strains, which are able to produce CLA in vitro, as starter cultures for milk fermentation, and no significant increase in CLA content was observed, even with sufficient amounts of LA. This result is in accordance with the prior study (Gorissen et al, 2011), suggesting that the availability of free FA was likely too low.…”
Section: Optimization Of Cla Production In Yogurtmentioning
confidence: 99%